Biosaka Pertanian Organik di Desa Banyior - Yoga Oktavian; Jakfar Sodik; Putri Hardiyanti; Rudi Nur Cahyo; Baytur Adistiya Oktavia; Muhammad Da’fal; Sholikhatus Hidayati; Puri Rahayu Setyo Ningsih (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
The many problems with subsidized fertilizers and the long-term effects of inorganic fertilizers on the environment mean that farmers have to think about other alternatives to overcome their agricultural problems. Therefore, it is important to carry out outreach and training activities on biosaka production involving farmers. Training activities were carried out in Banyior Village, Sepulu District, Bangkalan Regency on January 8 2024. The methods used were guidance and the learning by doing method. The process of implementing biosaka training is divided into 3 stages, namely the preparation stage, biosaka counseling stage, and biosaka making training. The result of this entire series of activities is that all participants in the extension and training on biosaka production were able to apply biosaka to their agricultural land. Farmers can also find out the tools and materials for making biosaka solutions. And farmers gain knowledge about the stages of making biosaka so that later they can make their own biosaka solution.